“So, that’s sort of wonderful”: The Ideology of Commitment and the Labor of Contingency - Sarah V. Seeley (Journal of the Assembly for Expanded Perspectives on Learning, 2020)
This article explores the emotional outcomes related to language commodification within an organizational context: the first-year writing program at Binghamton University, which is a public research university in upstate New York. In this setting, the meanings of effective writing instruction are discursively constructed in terms of a multi-faceted commitment to ‘the process.’ This entails an ideological commitment to both recursive process writing and the process of collaboratively evaluating the product that derives from it. I first offer an overview of the Binghamton context, including the details of collaborative portfolio assessment. I then analyze a specific sociolinguistic strategy: pep talking. I argue that pep talking is integral to cultivating localized technologies of the self through simultaneously bolstering the ideology of commitment and effacing instructors’ emotional outcomes.
Keywords: Education; Emotional Labor; Ideology of Commitment; Recursive process writing; Pep Talking